State- or trait-like individual differences in dream recall: preliminary findings from a within-subjects study of multiple nap REM sleep awakenings - Scarpelli, Serena; Marzano, Cristina; D’Atri, Aurora; Gorgoni, Maurizio; Ferrara, Michele; De Gennaro, Luigi (Frontiers in Psychology, 2015)
We examined the question whether the role of EEG oscillations in predicting presence/absence of dream recall (DR) is explained by “state-” or “trait-like” factors. Six healthy subjects were awakened from REM sleep in a within-subjects design with multiple naps, until a recall (REC) and a non-recall (NREC) condition were obtained. Naps were scheduled in the early afternoon and were separated by one week. Topographical EEG data of the 5-min of REM sleep preceding each awakening were analyzed by power spectral analysis [Fast Fourier Transform (FFT)] and by a method to detect oscillatory activity [Better OSCillations (BOSC)]. Both analyses show that REC is associated to higher frontal theta activity (5-7 Hz) and theta oscillations (6.06 Hz) compared to NREC condition, but only the second comparison reached significance. Our pilot study provides support to the notion that sleep and wakefulness share similar EEG correlates of encoding in episodic memories, and supports the “state-like hypothesis”: dream recall may depend on the physiological state related to the sleep stage from which the subject is awakened rather than on a stable individual EEG pattern.